Comment on "how the huge energy of quantum vacuum gravitates to drive the slow accelerating expansion of the Universe" - Mazzitelli, Francisco Diego (2018)
In a recent paper [Q. Wang, Z. Zhu, and W. G. Unruh, Phys. Rev. D 95, 103504 (2017)PRVDAQ2470-001010.1103/PhysRevD.95.103504] it was argued that, due to the fluctuations around its mean value, vacuum energy gravitates differently from what was previously assumed. As a consequence, the Universe would accelerate with a small Hubble expansion rate, solving the cosmological constant and dark energy problems. We point out here that the results depend on the type of cutoff used to evaluate the vacuum energy. In particular, they are not valid when one uses a covariant cutoff such that the zero-point energy density is positive definite.